2013
DOI: 10.1088/1674-4527/13/8/003
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical analysis for the formation of glycine in the interstellar medium

Abstract: Glycine (C 2 H 5 NO 2) was the first amino acid to be detected in space by the stardust space probe in Comet Wild2, and is used by living organisms to make proteins. We discuss three different reaction paths for the formation of glycine in interstellar space from some simpler molecules detected in the interstellar medium. The possibility of the formation of glycine in interstellar space is considered by radicalradical and radical-molecule interaction schemes using quantum chemical calculations with density fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…More recently, several studies have proposed other mechanisms for glycine production in the interstellar medium. For instance, Singh et al (2013) discussed three different reaction paths in the gaseous phase as well as in water-dominated ices that coat interstellar dust,…”
Section: Glycinementioning
confidence: 99%
“…More recently, several studies have proposed other mechanisms for glycine production in the interstellar medium. For instance, Singh et al (2013) discussed three different reaction paths in the gaseous phase as well as in water-dominated ices that coat interstellar dust,…”
Section: Glycinementioning
confidence: 99%
“…These reactions are series of hydrogenation processes to HCN on grains, as summarized in Table 3. 3. We have included the glycine formation on the grains from Singh et al (2013) via sequences of reactions with simple species, which are abundant in the ISM. They showed following possible routes to form glycine via quantum chemical calculations:…”
Section: Developed Chemical Network For Glycinementioning
confidence: 99%
“…While the reactions (2) was employed in Garrod (2013), Singh et al (2013) suggested the new reaction sequences to finally form glycine involving CH 2 CO, NH 2 CH 2 CO, and NH 2 CHCO. We tested the importance of these reaction sequence for the first time.…”
Section: Developed Chemical Network For Glycinementioning
confidence: 99%
See 1 more Smart Citation
“…The chemical analysis calculates the energy requirement for the reaction path; all calculations were performed at a temperature of 273.25 K and 1 atmospheric pressure. It has also been concluded that the proposed reactions, which are feasible and exothermic at this temperature and pressure, can also have a high probability of occurrence at low temperatures (∼100 K) and pressure (≤1 atm) in interstellar space (Singh et al 2013). The results depend on the conditions of the environment such as radiation field, temperature, and pressure, but our study gives qualitative indicators for serine formation in the ISM.…”
Section: Methodsmentioning
confidence: 96%